2014
DOI: 10.1111/cge.12365
|View full text |Cite
|
Sign up to set email alerts
|

Myhre syndrome

Abstract: Myhre syndrome (MS) is a developmental disorder characterized by typical facial dysmorphism, thickened skin, joint limitation and muscular pseudohypertrophy. Other features include brachydactyly, short stature, intellectual deficiency with behavioral problems and deafness. We identified SMAD4 as the gene responsible for MS. The identification of SMAD4 mutations in Laryngotracheal stenosis, Arthropathy, Prognathism and Short stature (LAPS) cases supports that LAPS and MS are a unique entity. The long-term follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 48 publications
(163 reference statements)
0
28
0
Order By: Relevance
“…Including our series of 4 patients reported here, 2 of which had previously been described by Lindor et al, the total number of cases of MLS reported in the literature is now 63 [1][2][3][4]7,8]. Of these patients, 8/63 (13%) had laryngotracheal stenosis reported as a manifestation of their disease including the 4 patients described above.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Including our series of 4 patients reported here, 2 of which had previously been described by Lindor et al, the total number of cases of MLS reported in the literature is now 63 [1][2][3][4]7,8]. Of these patients, 8/63 (13%) had laryngotracheal stenosis reported as a manifestation of their disease including the 4 patients described above.…”
Section: Discussionmentioning
confidence: 61%
“…Two patients (case 1 and case 2) have been described previously at the authoring institution and been reviewed by others [2,3]. In addition, we present two new adult cases of MLS (case 3 and case 4) that have never previously been reported in the literature.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Other features include developmental delay with mental retardation or/and behavioral disturbance, cardiac defects, cryptorchidism and bone anomalies. Skeletal manifestations include thickened calvarium, cone-shaped epiphyses, shortened tubular bones, hypoplastic iliac wings, broad ribs and large vertebrae with short and large pedicles 42,43 (Figure 3). All reported MS cases are sporadic, and advanced paternal age at birth has been reported, supporting de novo dominant mutations.…”
Section: Le Goff and V Cormier-dairementioning
confidence: 99%